Expatriate categorisation and evaluation: an empirical investigation in Poland and India. (1st January 2012) - Varma, Arup; Grodzicki, Jacek P.; Pichler, Shaun; Kupferer, Shannon; Ramaswami, Aarti
Using data from 205 Host Country Nationals (HCNs) (100 in Poland and 105 in India), we examined the impact of nationality and performance standards information on HCN willingness to provide role information, and their evaluations of expatriate colleagues. Results confirmed that both nationality and performance standards information were significantly related to HCN willingness to provide role information. However, nationality was not significantly related to task or trait type performance ratings, but when performance standards were provided, expatriates were given more favourable trait ratings than HCNs. We discuss the results in terms of their theoretical and practical implications.